Impact of Periodic Body Acceleration on Fractional Blood Flow Modeled as a Non-Newtonian Jeffery-Type Fluid in Stenosed Arteries - Shehu Adamu Aliyu; Habujika Abdulhadi Ismail (Mikailalsys Journal of Advanced Engineering International, 2026)
This study comprehensively explores the impact of hemodynamic parameters on nanoparticle transport and blood flow dynamics in stenosed arteries, with the objective of identifying how these parameters can be manipulated to improve targeted drug delivery and circulatory function in regions affected by vascular constriction. A mathematical model was formulated that incorporates externally induced factors, including baseline blood flow rates, the pulsatile nature of cardiac-induced oscillations, phase angles between these oscillations and the flow, and externally applied periodic body acceleration (PBA). The analysis reveals that increasing baseline blood flow enhances the distribution of oxygen and nutrients throughout the arterial system, highlighting the importance of optimized base flow conditions for maintaining tissue perfusion in stenotic regions. The incorporation of pulsatile flow characteristics that mimic natural heartbeat-induced oscillations leads to improved shear stress distribution along arterial walls, which may help prevent plaque formation and reduce the progression of arterial narrowing. Variations in phase angle, representing the temporal shift between flow oscillations and external stimuli, were shown to influence the synchronization between blood flow and externally applied forces, with consequent effects on hemodynamic efficiency and the timing of flow responses in stenosed vessels. Furthermore, the introduction of PBA substantially increases nanoparticle mobility within the bloodstream, reducing the likelihood of particle stagnation in low-flow regions and enhancing the efficiency of nanoparticle-based drug delivery. Overall, the findings underscore the potential of optimizing fluid dynamic parameters and employing PBA as a non-invasive strategy to augment drug perfusion and support vascular health, providing a theoretical basis for the development of more effective targeted cardiovascular therapies and motivating future translational studies to assess clinical feasibility and therapeutic efficacy.